Ground Water Quality Analysis in the Coastal of Bengkalis City Using Geochemistry Approach - Mairizki, Fitri; Cahyaningsih, Catur (-)
Disproportion between supply and demand of clean water is a complex problem in water management, especially in the coastal of Bengkalis city. Water scarcity occurs in different parts of the region accompanied by bad quality of ground water. Therefore, it is necessary to study the potential of groundwater as clean water and drinking water using geochemistry approach. Groundwater samples obtained from wells and wells drilled in Bantan Tua village, Bengkalis district, Riau. Most groundwater samples did not meet the requirements of clean water and drinking water based on Permenkes 492/Menkes/Per/IV/2010 in terms of physical and chemical parameters with temperatures ranging from 26-29oC, turbidity 5- >100 NTU, TDS 0-30,5 mg/L, pH 4,05â7,40, Cd 0,001-0,011 mg/L, Mn 0,020â1,775 mg/L, Fe 0,291â17,100 mg/L, Cu 0,000â0,095 mg/L, Cr < 0,05 mg/L, hardness 19,669â560,184 mg/L, SO42- < 25 mg/L, NO3- 17,96â220,6 mg/L, NH4+ 0,00â3,21 mg/L, F- < 0,10â 0,13 mg/L dan Cl- 0,2â71,8 mg/ L. TheÂ  groundwater in this study was dominated by non carbonate in form ofÂ  Na+K indicates that the facies of groundwater aquifers was influenced by seawater with clay lithology and illite mineralogy. The genesis of origin rocks derived from weathering igneous rock which rich in plagioclase and feldspar minerals.